2020
DOI: 10.1039/c9sc06203c
|View full text |Cite
|
Sign up to set email alerts
|

DNA nanotweezers for stabilizing and dynamically lighting up a lipid raft on living cell membranes and the activation of T cells

Abstract: We report a DNA nanotweezer that recruits raft-associated lipids, proteins and possibly endogenous cholesterol on living cell membrane. The DNA nanotweezers could activate T cell proliferation in a nonspecific activation manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Many studies have suggested that MβCD could remove cholesterol from rafts to induce significant changes in the physical properties of the plasma membrane by changing the distribution of raft associated proteins. 26 As shown in Fig. 4B , the clustering of Cy5 suggested that the HCR product, a DNA duplex, was not influenced by the MβCD treatment.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Many studies have suggested that MβCD could remove cholesterol from rafts to induce significant changes in the physical properties of the plasma membrane by changing the distribution of raft associated proteins. 26 As shown in Fig. 4B , the clustering of Cy5 suggested that the HCR product, a DNA duplex, was not influenced by the MβCD treatment.…”
Section: Resultsmentioning
confidence: 78%
“…To consolidate that the Cy5 lightened aggregates are associated with the lipid raft region, we performed control experiments by staining the HCR-treated cells with FITC-labeled CD59 and transferrin receptor (TfR) antibodies, respectively. CD59 is a glycosylphosphatidylinositol (GPI)-anchored membrane protein, 26 while the transferrin receptor (TfR) is an extensively studied non-lipid component. 28 A strong overlapping of CD59 with the Cy5 lightened aggregates was observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…c) The cholesterol‐modified DNA nanotweezers to manipulate cholesterol distribution on a living cell membrane. [ 121 ] Reproduced under terms of the Creative Commons CC‐BY license. Copyright 2020, The Authors, published by the Royal Society of Chemistry.…”
Section: Investigate Membrane Proteins Behaviors By Dna Nanostructuresmentioning
confidence: 99%
“…Copyright 2016, American Chemical Society. c) The cholesterol-modified DNA nanotweezers to manipulate cholesterol distribution on a living cell membrane [121]. Reproduced under terms of the Creative Commons CC-BY license.…”
mentioning
confidence: 99%
“…In another attempt to apply the lipid-DNA conjugate for studying lipid domains, Sun et al . used cholesterol-modified DNA duplexes to stabilize lipid domains on the cell membranes (Sun et al ., 2020 b ). The authors demonstrated that such stabilization of lipid domains can be used to induce membrane aggregation of the TCR-CD3 complex and to activate T-cell proliferation.…”
Section: Lipid-dna Conjugates For Studying the Biophysical Features O...mentioning
confidence: 99%